Effect of surfactant HLB value on Methane hydrate formation in non-ionic surfactant-oil water emulsions systems. (February 2019) - Liu, Zaixing; Liu, Weiguo; Lang, Chen; Li, Yanghui
Abstract: The methane hydrate formulation in emulsion is an important factor affecting the blockage of the subsea oil and gas transportation pipeline. In this study, to understanding the behavior of methane hydrate in different emulsion and the influence of surface active components, emulsions with the different hydrophilic lipophilic balance (HLB) value of surfactant mixture were prepared with mineral oil, deionized water and two kinds of non-ionic surfactant (Span80 and Tween80) with different rat io. And the format ion kinetics of methane hydrate in different emulsion was measured using pressure-volume-temperature (PVT) method. The experimental results demonstrate that the surfactant HLB value has a great influence on methane hydrate formulation in non-ionic surfactant-oil water emulsions systems. It could be divided into three parts. When the HLB value is below8, the emulsion is water-in-oil emulsion, and the hydrate is easy to form with the hydrophilic increasing. And methane hydrates are most likely to generated with the HLB value range from 8 to 10. And when the HLB value above 10, the emulsion is oil-in-water, and the methane hydrate is hard to form in the emulsion with 30vol% water as the continuous phase.